2019
DOI: 10.1101/801761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dendrites with specialized glial attachments develop by retrograde extension using SAX-7 and GRDN-1

Abstract: Dendrites develop elaborate morphologies in concert with surrounding glia, but the molecules that coordinate dendrite and glial morphogenesis are mostly unknown. C. elegans offers a powerful model for identifying such factors. Previous work in this system examined dendrites and glia that develop within epithelia, similar to mammalian sense organs. Here, we focus on the neurons BAG and URX, which are not part of an epithelium but instead form membranous attachments to a single glial cell at the nose, reminiscen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 86 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…We obtained the reference allele for this gene, the deletion strain ev505 , and characterized sense organ perturbations in detail (Nash et al, 2000). In previous work, we identified the gene grl-18 , which encodes for a poorly characterized protein that contains a ground-like domain, as well as col-53 and col-177 , which both encode collagens, as highly specific markers for ILso glia (Cebul et al, 2020; Fung et al, 2020). Using these markers, we find that 100% of unc-130 mutants lost expression of all three known ILso markers ( grl-18 pro, col-53 pro, and col-177 pro) specifically in one or both dorsal ILso glia (ILsoD), but not in lateral (ILsoL/R) or ventral (ILsoV) glia (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained the reference allele for this gene, the deletion strain ev505 , and characterized sense organ perturbations in detail (Nash et al, 2000). In previous work, we identified the gene grl-18 , which encodes for a poorly characterized protein that contains a ground-like domain, as well as col-53 and col-177 , which both encode collagens, as highly specific markers for ILso glia (Cebul et al, 2020; Fung et al, 2020). Using these markers, we find that 100% of unc-130 mutants lost expression of all three known ILso markers ( grl-18 pro, col-53 pro, and col-177 pro) specifically in one or both dorsal ILso glia (ILsoD), but not in lateral (ILsoL/R) or ventral (ILsoV) glia (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We focused on the development of the IL socket glia which are six-fold radially symmetric, such that there is a dorsal, lateral, and ventral pair of cells (ILsoD, ILsoL/R, ILsoV, respectively) (Mizeracka & Heiman, 2015). We recently identified specific markers for ILso glia and determined a role for them during dendrite extension of associated sensory neurons (Cebul et al, 2020). ILso glia develop via convergent differentiation - all three pairs of cells arise from distinct lineages that diverge at early stages of embryogenesis (Sulston et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, transgenic wild-type copies of sax-7S (+) expressed pan-neuronally (P unc-14::sax-7S, Prab-3::sax-7S ) rescue sax-7 mutant defects including head ganglia disorganization ( Fig. 2A ), PVQ axon flip-over, AIY and AVK neuronal soma displacement (Pocock et al, 2008), AIY soma position and branching (Diaz-Balzac et al, 2015), AFD neuronal soma position (Sasakura et al, 2005) and PVD length or defasiculation (Ramirez-Suarez et al, 2019), as well as neuronal SAX-7 expression rescues dendrite retrograde extension (Cebul et al, 2020). Interestingly, we observed that sfGFP::SAX-7S expression levels vary among specific neurons in a given animal, and these neuron-specific differences appear to be reproducible across animals.…”
Section: Discussionmentioning
confidence: 99%
“…sax-7 /L1CAM is well known to contribute to the development of distinct neurons in C. elegans . It is involved in dendrite development and axon guidance (Cebul et al, 2020; Chen et al, 2019; Diaz-Balzac et al, 2015; Diaz-Balzac et al, 2016; Dong et al, 2013; Heiman and Pallanck, 2011; Ramirez-Suarez et al, 2019; Salzberg et al, 2013; Schafer and Frotscher, 2012; Sherry et al, 2020; Yip and Heiman, 2018; Zhao et al, 1998; Zhu et al, 2017). In flies and mammals, homologues of sax-7 function in neuronal migration, axon guidance, and synaptogenesis (Bieber et al, 1989; Godenschwege et al, 2006; Hall and Bieber, 1997; Rougon and Hobert, 2003; Sonderegger et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, knockdown of a chromatin remodeler Drosophila homolog of the human alpha‐thalassemia and mental retardation X‐linked protein (dATRX) prevents somatodendritic ensheathment of class IV dendritic arborization neurons during development which then changes dendrite density and decreases regenerative potential (Yadav et al, 2019). A recent study in Caenorhabditis elegans identified that the cytoplasmic expression of glial protein girdin homolog ( grdn‐1 ), whose mammalian homolog is crucial for proper brain development, is required non‐autonomously to anchor and stretch dendrites retrograde from their targets in the nose during embryo elongation (Cebul, McLachlan, & Heiman, 2020), supporting an early role of glia in regulating dendrite morphology.…”
Section: Early Specification and Migrationmentioning
confidence: 99%